Smallwood Interview 08A - Memorial University of Newfoundland. Educational Television Centre (Memorial University of Newfoundland. Educational Television Centre, 1983)
In this session with Robert Pitt, Joseph (Joey) Smallwood talks about his failures and successes in life, stressing that for him success was never defined by monetary wealth or affluence. but rather by intelligence and knowledge. He discusses his life between the ages of twenty-five and forty-five; recalls his days in New York City and how he developed and strengthened his self-confidence. Smallwood walked across Newfoundland and also drove the first car across the island.